2020
DOI: 10.7150/jca.38624
|View full text |Cite
|
Sign up to set email alerts
|

Curcumol inhibits the proliferation and metastasis of melanoma via the miR-152-3p/PI3K/AKT and ERK/NF-κB signaling pathways

Abstract: Melanoma is the most aggressive and treatment-resistant form of skin cancer. Curcumol is a Chinese medicinal herb traditionally used as a cancer remedy. However, the molecular mechanisms underlying the anticancer activity of curcumol in melanoma remains largely unknown. In the present study, we observed that Curcumol decreased mouse melanoma B16 cell proliferation and migration. The xenograft tumor assay showed that curcumol reduced melanoma volume and lung metastasis. Curcumol upregulated the expression of E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…It has been revealed that microRNA (miR)-1224-5p inhibited metastasis and EMT in colorectal cancer by targeting the SP1-mediated NF-κB signaling pathways ( 41 ). In addition, curcumol could inhibit the proliferation and metastasis of melanoma via the miR-152-3p/PI3K/AKT and ERK/NF-κB signaling pathways ( 42 ). In the present study, mechanism analysis via western blotting demonstrated that CGA significantly downregulated the expression levels of NF-κB-associated proteins and EMT process-associated proteins, indicating that CGA impaired NF-κB, and then inhibited the EMT signaling pathway, thereby suppressing breast cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that microRNA (miR)-1224-5p inhibited metastasis and EMT in colorectal cancer by targeting the SP1-mediated NF-κB signaling pathways ( 41 ). In addition, curcumol could inhibit the proliferation and metastasis of melanoma via the miR-152-3p/PI3K/AKT and ERK/NF-κB signaling pathways ( 42 ). In the present study, mechanism analysis via western blotting demonstrated that CGA significantly downregulated the expression levels of NF-κB-associated proteins and EMT process-associated proteins, indicating that CGA impaired NF-κB, and then inhibited the EMT signaling pathway, thereby suppressing breast cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The activated PI3K/AKT pathway has been mentioned in skin cancer carcinogenesis, 26 and the PI3K/AKT pathway deficit can partially attenuate melanoma progression. 27 Moreover, the PI3K/AKT/mTOR pathway was displayed by Nardo et al to play an indispensable role in the pathogenesis of CSCC. 14 A recent study indicated that miR-21 directly targets and inhibits the expression of PTEN (a negative modulator of the PI3K/AKT pathway), and miR-21 inhibition upregulated PTEN expression but impaired the PI3K/AKT pathway, thereby elevating liver cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that TTN-AS1 knockdown inhibited the invasive and migratory abilities of both MDA-MB-453 and MDA-MB-231 cells, which was reversed by transfection with the miR-211-5p inhibitor. MMPs, including MMP-2 and MMP-9, are major components that are implicated in invasion and migration, and the upregulation of these proteins is closely associated with the aggressiveness and metastasis of TNBC ( 32 34 ). In the present study, decreased MMP-2 and MMP-9 expression was observed following TTN-AS1 knockdown, which was reversed following transfection with the miR-211-5p inhibitor.…”
Section: Discussionmentioning
confidence: 99%